2008
DOI: 10.1160/th08-01-0006
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of ADAMTS13 in patients with liver cirrhosis

Abstract: Decreased plasma ADAMTS13 activity (ADAMTS13:AC) results in the accumulation of unusually large von Willebrand factor multimer (UL-VWFM) and the formation of platelet thrombi. It remains controversial whether or not plasma ADAMTS13:AC decreases in patients with liver cirrhosis (LC), and its relationship to clinical features has not been fully investigated. We measured ADAMTS13:AC and its related parameters in plasma in 33 patients with chronic hepatitis (CH) and in 109 patients with LC. ADAMTS13:AC decreased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 56 publications
(76 reference statements)
6
55
0
Order By: Relevance
“…None of the hepatitis patients in this study were reported to have cirrhosis, which may suggest that lower levels of this protease may only be seen upon progression of the medical condition. This is confirmed by results of other studies where a decrease of ADAMTS-13 activity was evident with increasing severity of liver disease and liver cirrhosis [13,22,23]. We also found that ADAMTS-13 antigen levels were lower in patients compared to controls; however, the decrease was not statistically significant (p = 0.08).…”
Section: Discussionsupporting
confidence: 91%
“…None of the hepatitis patients in this study were reported to have cirrhosis, which may suggest that lower levels of this protease may only be seen upon progression of the medical condition. This is confirmed by results of other studies where a decrease of ADAMTS-13 activity was evident with increasing severity of liver disease and liver cirrhosis [13,22,23]. We also found that ADAMTS-13 antigen levels were lower in patients compared to controls; however, the decrease was not statistically significant (p = 0.08).…”
Section: Discussionsupporting
confidence: 91%
“…Plausible explanations include increased factor VIII levels due to increased endothelial cell activation/injury, decreased ADAMTS13 activity, or increased levels of platelets and fibrinogen as “acute phase reactants.” In fact, platelet counts tended to be higher in patients with ALF compared to ALI (200 vs. 150 × 10 9 /L, respectively; P =0.09) and correlated directly with ammonia ( r =0.30; P =0.031). ADAMTS13, a protease synthesized in hepatic stellate cells, degrades highly active, large multimers of von Willebrand factor (vWF) [26], and is decreased in proportion to the severity of chronic liver failure [27]. Conceivably, patients with ALF may be deficient in ADAMTS13, leading to an accumulation of large vWF multimers, and consequently to an increase in TEG parameters which reflect platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ~10% of patients with severe cirrhosis (Child class C) may have ADAMTS13 activity <10%. 34 However, preexisting cirrhosis does not exclude the possibility of typical acquired TTP with severe ADAMTS13 deficiency that will respond to plasma exchange.…”
Section: Conditions Other Than Ttp That May Affect Adamts13mentioning
confidence: 99%